The Strategic Role of the Third Mission in Universities A Concrete Case Study - Rusciano, Rosamaria (European Scientific Journal, ESJ, 2024)
Purpose - In addition to teaching and research, the universities aim to contribute to the development of civil society by promoting the direct application, valorisation and use of knowledge. In reality, it is a widespread and shared opinion that it is no longer enough to carry out research within the university perimeter and publish subsequent works in scientific journals, nor can we be satisfied only with teaching children in university courses. Design/ methodology / approach - The methodology used is qualitative as the research question essentially was: how was the Third Mission (TM) included in the strategic choices of the Universities? In light of the new methods of evaluating universities, how can we highlight what they have done in terms of the third mission? Are organizational solutions possible in the approach to TM? Findings - The objective was to verify what the impact and future development of the Third Mission in the Universities will be. In light of its inclusion among the evaluation criteria of universities and teachers, the third mission represents the new frontier of the future in terms of local and national openness and development, as well as their economic and financial sustainability. To this end, the analysis of a case is proposed, as a best practice, and in particular the case of the Department of Business and Legal Sciences of the University of Calabria is presented. Originality / value – The application and implementation of rules and regulations is always difficult in any case and in any field, let’s imagine in public administration and universities, bureaucratically "plastered" and not very inclined to change and innovation, especially regarding performance evaluation.